Assessment of immunization coverage and associated factors among children in Paravur Taluk of Ernakulam district, Kerala - Kizhatil, Anuradha; ., Reshma; Hariharan, Harsha Chollankil; John, Alexander; Thomas, Ann Mary; Padmanabhan, Gopalakrishnan (International Journal Of Community Medicine And Public Health, 2019)
Background: Immunization is one of the most cost-effective interventions averting countless childhood deaths and protecting millions of children from disability and illness. The objective of the current study was to assess the immunization coverage and associated factors among children aged 12-23 months and 5-7 years in Paravur Taluk of Ernakulam district, Kerala. Methods: A community based cross sectional study was done. Cluster sampling method of WHO was used for evaluation of immunization coverage.300 children in the age group of 12–23 months and 300 children in the age group 5-7 years were selected from each of the 30 clusters. Crude coverage details for each vaccine were estimated using percentages. Bivariate analysis was conducted to identify independent predictors of immunization coverage. Results: Among the children 12-23 months old, eleven (3.7%) children were partially immunized, while everybody had received at least one vaccine. The proportion of children fully immunized was 96.3%. Among the children 5-7 years old 55 (18.3%) were partially immunized. Belonging to Muslim religion, fathers’ occupation i.e. who were labourers/unskilled workers, mother’s education less than 12th standard and not possessing the mother and child protection card were found to be factors associated with partial immunization. Conclusions: This study shows that full immunization has not reached all children.